Photon dynamics in metal insulator anisotropic active and passive systems - Aniket, Patra; Cipparrone, Gabriella; Caligiuri, Vincenzo (Università della Calabria, 2023)
In this thesis, we analyzed the photon dynamics in different metal-dielectric anisotropic structures theoretically as well as experimentally, with and without embedded gain materials. The simplest system is a metal-dielectric bilayer that acts as an open cavity and can support some optical modes, which we call pseudo-cavity modes. This system can be used to study strong light matter interaction, which is demonstrated by placing an optical active material or gain medium on top of the open cavity. Since in such an open cavity structure the gain material is directly accessible to the optical stimulation (for example a pump laser), the photoluminescence from the active material can be straightforwardly enhanced. This open cavity also preserves the polarization state, which enables such structures as polarization dependent optical sources. A Metal-Dielectric-Metal (MDM) structure forms a closed cavity with two reflective metal layers. In recent studies, it has been shown that such structures support epsilon near zero (ENZ) modes, and such vanishing dielectric permittivity triggers numerous intriguing new properties such as: cloaking with negative refractive index, Purcell factor enhancement, energy squeezing and electric levitation, etc. In our work, we fabricated MDM cavities and demonstrated the polariton generation inserting a light emitting gain material inside the dielectric layer. By matching the ENZ cavity resonance with gain medium we obtained strong coupling, and found that the polaritons in this system maintained the ENZ properties of the MDM cavity. In the second part of the work, the photon dynamics in the extreme anisotropic medium are analyzed without an embedded gain medium. With the help of a combined system composed of open and closed cavities, a strong plasmonic PUF (Physical Unclonable Function) has been demonstrated for practical application. With the help of a morphology study of the plasmonic materials and image processing, high-level anticounterfeiting functionality of silver nano island on top of MDM cavities is demonstrated. The photon dynamics in another highly anisotropic system are investigated by combining two different optical resonators, a MDM cavity and a Guided mode resonance (GMR) cavity. The origin of the strong coupling regime occurring in a GMR-MDM architecture has been investigated numerically and experimentally. The role of the polarization of the incident light on the strong coupling between the modes is investigated and plausible applications such as polarization-sensitive switching are discussed.
Università della Calabria. Dipartimento di Fisica. Dottorato di ricerca in Scienze Fisiche, Chimiche e dei Materiali. Ciclo XXXV
Keywords: Light matter interaction; Strong coupling; Anisotropic medium; Cavities